Size-dependent magnetic properties of nanocrystalline yttrium iron garnet powders - Rajendran, M.; Deka, Sasanka; Joy, Pattayil Alias; Bhattacharya, Asish K. (Journal of Magnetism and Magnetic Materials, 2006)
Yttrium iron garnet (YIG) powders with particle sizes of 9, 14, 25 and 60 nm have been synthesised and their magnetic properties have been studied as a function of particle size and temperature. The particles with sizes of 9 and 14 nm exhibited superparamagnetism. The blocking temperature (T-B) decreased with decreasing particle size, whereas the anisotropy constant (K) increased. The saturation magnetisation (M-s) decreased with decreasing particle size. These variations are attributed to large surface-to-volume ratios in nanoparticles where the surface moments are predominant. (c) 2005 Published by Elsevier B.V.
Keywords: anisotropy constant; Magnetism; Nanoparticles; Superparamagnetism; YIG

Superparamagnetic nanocrystalline ZnFe2O4 with a very high curie temperature - Deka, Sasanka; Joy, Pattayil Alias (Journal of Nanoscience and Nanotechnology, 2008)
Studies on the magnetic properties of nanocrystalline ZnFe2O4 synthesized by an autocombustion method are reported. Superparamagnetic behavior is observed for the nanocrystalline materials with particle sizes of 8 nm and 17 nm, with superparamagnetic blocking temperatures of 65 K and 75 K, respectively. Magnetic hysteresis with very large coercivities of 533 Oe and 325 Oe, respectively, are observed at 12 K. Studies on the temperature variation of the magnetization above room temperature indicate that the Curie temperature is as high as similar to 800 K when compared to the paramagnetic nature of bulk zinc ferrite at room temperature.
Keywords: Curie temperature; Nanocrystalline; Superparamagnetism; Zinc Ferrite